ĐIỀU CHẾ BIODIESEL TỪ MỠ CÁ TRA VỚI XÚC TÁC BAZ RẮN KOH/γ-Al2O3 - Hương, Lê Thị Thanh; Tân, Phan Minh; Hoa, Trần Thị Việt (Vietnam Journal of Science and Technology, 2012)
BIODIESEL PRODUCTION FROM FAT OF TRA CATFISH BY KOH/γ-Al2O3 AS A SOLID-BASE CATALYST The objective of the project is to research the production of biodiesel from fat of Tra Catfish and methanol using K+/γ-Al2O3 as a solid-base catalyst. The results show that KOH/γ-Al2O3 prepared by loading KOH of 7 mmol on Al(OH)3 of 1 g, after being calcined at 550oC for 2 h, which can give the best catalytic activity for this reaction. The maximum conversion of 92,63% has been achieved after 90 minutes, at 60oC when the molar ratio of MeOH to tra fat is 8/1 and 6% KOH/γ-Al2O3 catalyst. The produced biodiesel met the required ASTM D6751 standard.